Editing of the Sendai virus P/C mRNA by G insertion occurs during mRNA synthesis via a virus-encoded activity. - Vidal, S (1990)
Two forms of the Sendai virus P/C mRNA have been predicted: one an exact copy of the viral genome, and the other with a single G insertion within a run of three G's. We directly cloned the mRNA or portions of it containing the insertion site and screened the resulting colonies with oligonucleotides that could distinguish the presence of three or four G's at this position. We found that 31% of the mRNAs did in fact contain the predicted insertion, whereas the viral genomes contained no heterogeneity at this position. A smaller fraction (7%) of the mRNA contained two to eight G's inserted at this position. The insertions also took place during RNA synthesis in vitro with purified virions but were not detected when the mRNA was expressed in vivo via a vaccinia virus recombinant. When the Sendai virus- and vaccinia virus-derived P/C mRNAs were coexpressed in the same cells under conditions in which each could be distinguished, those from the Sendai genome were altered as before, but those from the vaccinia virus genome remained unaltered. The activity that alters the mRNA is therefore likely to be coded for by the virus and cannot function in trans.